Giovanni Aldini and his contributions to non-invasive brain stimulation - Fernando Zanela da Silva ARÊAS; Guilherme Peixoto Tinoco ARÊAS; Roberto MOLL NETO (Arquivos de Neuro-Psiquiatria)
ABSTRACT Giovanni Aldini was an Italian physicist interested in propagating Galvanism. With his uncle, Luigi Galvani, he learned techniques of electrical stimulation in humans and helped him to develop them. He later developed his own ideas and created transcranial electric stimulation. This paper presents some of Aldini's personal and professional traits, showing his trajectory and how his performance was important for the development of non-invasive brain stimulation techniques as a whole. Through research on animals and, later, on cadavers, his fundamental discoveries at the beginning of the treatment proposals are used so far.